Моделювання марковських процесів відновлення працездатності систем - Антонець, О. М. (ХНУРЕ, 2023)
Purpose of the work is to optimize a "Human-Machine-Environment" (HME) system structure in the part that coresponds to disaster situations in order to reduce the response time. Several models of the HME systems, which have Markov property, are offered. With the help of queuing systems theory, a number of problems for the research and solution of HME have been identified. The model of the queuing system is the best suited for rescue sub-systems, for which the elimination of an accident is a "stationary condition." Transition and state probabilities of the appropriate Markov chain are determined using the socalled "Second Law of Synergetics."
Keywords: система «людинамашина-середовище»; шкідливі виробничі фактори; підсистема «машина»; підсистема «середовище»; підсистема «людина»